Comparison of proximal femoral universal nail and proximal femoral nail anti-rotation internal fixation for older patients with intertrochanteric femoral fracture: a retrospective cohort study - Cao, Yuan; Fan, Jixing; Cui, Zengzhen; Hao, Youliang; Lai, Shengtao; Tian, Yun; Lv, Yang; Zhou, Fang (Frontiers in Medicine, 2025)
IntroductionIntertrochanteric femoral fractures (IFF) are among the most common lower limb fractures in the older population. Our team has developed a new cephalomedullary nail design called the proximal femoral universal nail (PFUN). This study aimed to compare the clinical outcomes of PFUN and proximal femoral nail anti-rotation (PFNA) internal fixation for the treatment of IFF in older patients.MethodsWe retrospectively reviewed the clinical records of 435 older patients with IFF who were treated at Peking University Third Hospital between January 2022 and January 2024. Among them, 215 underwent PFUN (PFUN group) and 220 underwent PFNA (PFNA group) internal fixation. Demographic data, operation time, hospitalization time, blood loss, intraoperative transfusion, complications, Harris hip scores (HHS), and Parker-Palmer mobility scores (PPMS) were compared between the two groups.ResultsThe two groups were comparable in terms of demographic data (p > 0.05). The operation time in the PFNA group was shorter than that in the PFUN group, and blood loss was less than that in the PFUN group (p < 0.05). However, the hospitalization time was shorter in the PFUN group than in the PFNA group (p < 0.05). At 3 and 6 months postoperatively, the HHSs of the PFUN group were significantly higher than those of the PFNA group, and similar results were obtained for PPMS at 6 months postoperatively (p < 0.05). Nevertheless, we found no difference between the groups in the HHSs and PPMSs at 12 months postoperatively or at the final follow-up (p > 0.05). The rate of fixation failure in the PFUN group was significantly lower than that in the other groups (p < 0.05), whereas there was no significant difference in the rate of other general complications (p > 0.05). Among patients with AO/OTA classification 31-A2, the implant failure rate in the PFUN group was significantly lower than that in the other group, and the PPMS score at 6 months postoperatively was higher (p < 0.05). In the AO/OTA classification of 31-A3 stratification, the Harris score and PPMS score of the PFUN group during the postoperative follow-up period were higher than those of the PFNA group (p < 0.05).ConclusionThe PFUN is an effective and safe internal fixation device for IFFs, especially for unstable medial and lateral wall fractures. Compared to PFNA, PFUN can significantly reduce the rate of implant failure in IFFs and accelerate postoperative rehabilitation. For IFFs with AO/OTA classifications of 31-A2 and A3, PFUN has a greater advantage than PFNA.